Upaya Meningkatkan Kemampuan Passing Bawah dengan Modifikasi Permainan Passing Pantul Bola Voli pada Siswa Kelas V SD Negeri 6 Sinanggul Kecamatan Mlonggo Kabupaten Jepara (Universitas Negeri Semarang, 2021)
The lack of interest in the volleyball learning methord is based on the problem in this study, namely the effonrts to improve passing bouncing ability for fifth grade students of SD Negeri 6 Sinanggul. The hope is that by making modifications to these tools and games, male and fermale students can do physical education learning in a fun atmosphere. The subjects were all students of class V Elemtary School 6 Sinanggul, Tutaling 30 students,namely 10 fermale students and 20 male students. The object is efforts to improve lower passing ability by modifying bouncing passing in volleyball game for fifth grade students of SD Negeri 6 Sinanggul. The time of the research was carried out in cycles 1 and 2 with research procedyrs from planning. Implementing actions,and reflection. The location of the reseach procedure was carried out on the page of SD Negeri 6 Sinanggul,Mlonggo District,Jepara Regency. The data collection technique was in the from of collecting information from the cognitive,affective,and psychomotor domains. This research instrument uses lessons plans,observation sheets,students interviews,performance test and spss. Analysis using test scores. Based on the results of the study showed indications of improvement in the learning process from observation research sheets from physical education experts and teachers,and sheets from students assessments. Showing good results with a 35% cycle l and 65% cycle ll showing a high learning lm provement.this effort made by physical education teachers in solving this problem is to able to create simple games with jointly made rules and modify plastic balls with wood so that and movement. Thus,it can be suggested that pyhsical education learning through bouncing passing can be as an alternative to improve the physical educations learning process, especially in volleyball. Hopefully in the future the methods applied can be further developed to be better and produce quality learning.